2017
DOI: 10.3899/jrheum.161103
|View full text |Cite
|
Sign up to set email alerts
|

Severe Extraarticular Manifestations in a Community-based Cohort of Patients with Rheumatoid Arthritis: Risk Factors and Incidence in Relation to Treatment with Tumor Necrosis Factor Inhibitors

Abstract: This study suggests that patients treated with TNF inhibitors are at a slightly increased risk of developing severe ExRA. RF-positive patients with disabling disease of long duration were more likely to develop severe ExRA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 30 publications
0
6
0
1
Order By: Relevance
“…First, a relatively small proportion of patients with RA-ILD was included, so we had to be conservative while building our models because of the risk of overfitting, so residual confounding cannot be ruled-out. Treatment and disease activity were not included; the former due to concerns about the accuracy of timing and dosing and current literature’s inability to validate a true relationship between RA-ILD and methotrexate45 or bDMARDs 46–48. The latter, because of the design of the study with only a single measurement, which has not shown to be relevant in previous reports,49 50 as opposed to its longitudinal evaluation 51.…”
Section: Discussionmentioning
confidence: 99%
“…First, a relatively small proportion of patients with RA-ILD was included, so we had to be conservative while building our models because of the risk of overfitting, so residual confounding cannot be ruled-out. Treatment and disease activity were not included; the former due to concerns about the accuracy of timing and dosing and current literature’s inability to validate a true relationship between RA-ILD and methotrexate45 or bDMARDs 46–48. The latter, because of the design of the study with only a single measurement, which has not shown to be relevant in previous reports,49 50 as opposed to its longitudinal evaluation 51.…”
Section: Discussionmentioning
confidence: 99%
“…Bone destruction is primarily mediated by osteoclasts activated by ‘receptor activator of nuclear factor-κB’ (RANKL) and inflammatory cytokines in the synovial lining ( 10 ). If clinically manifested RA remains untreated or becomes treatment refractory, it can lead to extra-articular manifestations such as cardiovascular disease (CVD), interstitial lung disease, and increased risk of malignancy, due to increased immune complexes and acute phase response ( 37 ).…”
Section: Background: Rheumatoid Arthritismentioning
confidence: 99%
“…Myocarditis may be diffuse necrotizing or granulomatous. According to [ 18 ], the percentage of cardiomyopathy in patients with RA is believed to be 3–30%, discovered by autopsy. The precise etiopathogenesis of this disease is not fully understood, but some inflammatory cytokines (for example, interleukin (IL)-1α) and mediators are released from the degenerating myocardium, thus activating inflammatory corpuscles in other nearby cells [ 10 ].…”
Section: Cardiac Involvement In Rheumatoid Arthritismentioning
confidence: 99%